Uma infra-estrutura de apoio a um processo de medição de projetos em micro e pequenas empresas de software - Gustavo Monti Rocha (2009)
It is estimated that 77% of software companies in Brazil are micro and small companies (MSC). They play an important role in the economy attending software market segments that usually are not attended by large companies. However, about 96% get out of business during their first two years after establishment. One of the factors contributing to this high level of mortality is the lack of quality assurance of its products where the quality of the final product is largely determined by its production process. Generally they have an informal process of software production and, consequently, dependent primarily on the competence of those involved. One of the factors of success in improving the software production process is the presence of measuring activities. Thus, approaches such as GQM, GQIM and PSM have been developed, but in the form of generic models. These models are not easy to be used directly by MSCs. Based on these facts we decided to establish an MSC focused measuring infrastructure. Our infrastructure consists of a measuring process (PROMPES) and a supporting tool (FAM). As a study case PROMPES and FAM were applied in an MSC and we obtained an infrastructure with low effort and great benefits.